La transmisión y acumulación de bienes de consumo de la familia del jurado Eugenio de Yepes - María Trinidad López García (Centre de Recherches sur les Mondes Américains, 2008)
The carry out of our doctoral thesis about the transmission of the regidor’s job, and the researching we are making about the transmission of the jurado’s one, have let us to state the way of the transmission of the jurado’s job from one generation (in this case the marriage consisted of the jurado and his wife) and the way of the acquisition of several regidurías with the accumulated capital since several generations till this family got perpetuated into the elite of regidores. Taking as a basis the public notary protocols, and specifically, the wills, the inventory of goods, dowries,…, with a relevant and consolidated role for the historic researching, we want to show: which has been the heritage accumulation from the several members of this family (houses, lands,…) and how the reached purchasing power has allowed, and how much, the consumption in furniture, objects (metal, glass, wood), silver, pictures, books, fabrics, colours, …. In summary, what has been the family genealogy path of the jurado Eugenio Yepes who is the object of this study.